Data Management in Grid and Peer-to-Peer Systems 4th International Conference, Globe 2011, Toulouse, France, September 1-2, 2011, Proceedings - Hameurlain, Abdelkader; Tjoa, A Min.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Data Management in Grid and Peer-to-Peer Systems, Globe 2011, held in Toulouse, France, in September 2011 in conjunction with DEXA 2011. The 12 revised full papers presented were carefully reviewed and selected from 18 submissions. The papers are organized in topical sections on data storage and replication, semantics for P2P systems and performance evaluation, resource discovery and routing in mobile P2P networks, and data stream systems and large-scale distributed applications.
Keywords: Computer science; Software engineering; Database management; Information systems; Electronic data processing; Artificial intelligence; Information Systems; Computer Science; Computing Methodologies; Database Management; Software Engineering; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Management of Computing and Information Systems